Forced vibrations of a rod with attached tank which is partially filled with liquid - Trotsenko, Yu.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The axisymmetric structure, which consists of a rod and the tank attached to it, which is partially filled with an ideal liquid is considered. The study of forced vibrations of such a mechanical system under the influence of external forces and moments is reduced to the system of ordinary differential equations of a simple form. The independent variable in these equations is the time.